Long‐term dynamics in microbial eukaryotes communities: a palaeolimnological view based on sedimentary DNA. Issue 23 (10th November 2016) - Capo, Eric; Debroas, Didier; Arnaud, Fabien; Guillemot, Typhaine; Bichet, Vincent; Millet, Laurent; Gauthier, Emilie; Massa, Charly; Develle, Anne‐Lise; Pignol, Cécile; Lejzerowicz, Franck; Domaizon, Isabelle
Abstract: Assessing the extent to which changes in lacustrine biodiversity are affected by anthropogenic or climatic forces requires extensive palaeolimnological data. We used high‐throughput sequencing to generate time‐series data encompassing over 2200 years of microbial eukaryotes (protists and Fungi) diversity changes from the sedimentary DNA record of two lakes (Lake Bourget in French Alps and Lake Igaliku in Greenland). From 176 samples, we sequenced a large diversity of microbial eukaryotes, with a total 16 386 operational taxonomic units distributed within 50 phylogenetic groups. Thus, microbial groups, such as Chlorophyta, Dinophyceae, Haptophyceae and Ciliophora, that were not previously considered in lacustrine sediment record analyses appeared to be potential biological markers of trophic status changes. Our data suggest that shifts in relative abundance of extant species, including shifts between rare and abundant taxa, drive ecosystem responses to local and global environmental changes. Community structure shift events were concomitant with major climate variations (more particularly in Lake Igaliku). However, this study shows that the impacts of climatic fluctuations may be overpassed by the high‐magnitude eutrophication impacts, as observed in the eutrophicated Lake Bourget. Overall, our data show that DNA preserved in sediment constitutes a precious archive of information on past biodiversity changes.